Tenebriochernes, a new genus and species of Chernetidae (Arachnida: Pseudoscorpiones) from north-western Colombia, with ecological observations - Bedoya-Roqueme, Edwin; Torres, Richard A. (Zootaxa, 2019)
A new pseudoscorpion genus, Tenebriochernes n. gen., with the type species T. concavus n. sp. is described from two caves in northern Colombia, where it inhabits the dark zone of caves. Two additional new species T. mohani n. sp. and T. pilosus n. sp., are described from conserved dry forest areas and buffer zones. Sexual dimorphism of the pedipalps is evident, particularly in the length of appendages and the width of the hand. The new genus shows affinities with the genus Neoallochernes Hoff, 1947. A taxonomic key, distribution map and ecological comments are given.